Pengaruh Media Internet terhadap Perilaku Menyimpang Siswa di SMK al-Islam Kudus - Ba'agil, Maryam Usman (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2022)
Behavioral deviations committed by adolescents today are very diverse. This form of deviation is often found in media such as Facebook, the internet, television and newspapers, even in acts that violate the law. Based on this, it is necessary to know how the influence of the internet on behavioral deviations committed by adolescents, especially students at SMK Al-Islam Kudus. This research is included in the quantitative research with analytic survey method. The results showed that it was concluded that the independent variable (internet media) had no effect on deviant behavior, or in other words the regression model could be used to predict deviant behavior. In addition, it can also be concluded by comparing the significant values in the table above, namely 0.589 with α = 0.05 where sigcount > 0.05, so it can be concluded that the independent variable (internet media) has no effect on deviant behavior.